COЕXISTENSE OF KATHAREVUS AND DIMOTIC: COMPARATIVE ASPECT - Звонська, Леся (SWorldJournal, 2024)
The article examines the long-term coexistence of katharevus and dimotic in the development of the Greek language in the 19th and 20th centuries; socio-political and linguistic-literary approaches to solving the language issue are revealed; phonetic, mor